2019
DOI: 10.4049/jimmunol.1900216
|View full text |Cite
|
Sign up to set email alerts
|

ZBP1/DAI Drives RIPK3-Mediated Cell Death Induced by IFNs in the Absence of RIPK1

Abstract: Receptor-interacting protein kinase 1 (RIPK1) regulates cell fate and proinflammatory signaling downstream of multiple innate immune pathways, including those initiated by TNF-α, TLR ligands, and IFNs. Genetic ablation of Ripk1 results in perinatal lethality arising from both RIPK3-mediated necroptosis and FADD/caspase-8–driven apoptosis. IFNs are thought to contribute to the lethality of Ripk1-deficient mice by activating inopportune cell death during parturition, but how IFNs activate cell death in the absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 38 publications
3
44
0
Order By: Relevance
“…Firstly, cultured primary RIPK1 keratinocytes, grown in sterile conditions, succumb to IFN-induced necroptosis, which crucially depended on the nucleic acid sensing capability of ZBP1. This is in agreement with earlier studies reporting on the toxicity of IFNs for RIPK1-deficient fibroblasts (Dillon et al, 2014;Kaiser et al, 2014), and which was recently shown to depend on ZBP1 (Ingram et al, 2019;Yang et al, 2019). Secondly, embryos expressing a mutant RIPK1 RHIM develop ZBP1-RIPK3-MLKL driven inflammatory epidermal hyperplasia at embryonic day 18.5, before exposure to microbes at birth (Lin et al, 2016;.…”
Section: Zbp1 Activation By Endogenous Nucleic Acids Induces Necroptosupporting
confidence: 92%
“…Firstly, cultured primary RIPK1 keratinocytes, grown in sterile conditions, succumb to IFN-induced necroptosis, which crucially depended on the nucleic acid sensing capability of ZBP1. This is in agreement with earlier studies reporting on the toxicity of IFNs for RIPK1-deficient fibroblasts (Dillon et al, 2014;Kaiser et al, 2014), and which was recently shown to depend on ZBP1 (Ingram et al, 2019;Yang et al, 2019). Secondly, embryos expressing a mutant RIPK1 RHIM develop ZBP1-RIPK3-MLKL driven inflammatory epidermal hyperplasia at embryonic day 18.5, before exposure to microbes at birth (Lin et al, 2016;.…”
Section: Zbp1 Activation By Endogenous Nucleic Acids Induces Necroptosupporting
confidence: 92%
“…This observation suggests that OTULIN may also suppress the pathways that are responsible for the production of IFNs, either indirectly by preventing overall inflammation or by direct control of IFN production. In that context, FADD and RIPK1 have been identified as being implicated in an immune defense pathway against intracellular double-stranded RNA (dsRNA) (Balachandran et al, 2004;Michallet et al, 2008;Rajput et al, 2011;Ingram et al, 2019). Further studies are required to identify the pathway(s) regulated by OTULIN driving type I IFN production.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that OTULIN might also suppress pathways responsible for the production of interferons, either indirectly by preventing overall inflammation, or by direct control of interferon production. In that context, FADD and RIPK1 have been identified as being implicated in an immune defense pathway against intracellular dsRNA (Balachandran et al, 2004; Michallet et al, 2008; Rajput et al, 2011; Ingram et al, 2019). Further studies are required to identify the pathway(s) regulated by OTULIN driving type I interferon production.…”
Section: Discussionmentioning
confidence: 99%